Study Of Solid Planar Source For Phosphorus Diffution Process On Semiconductor Devices Fabrication - S. Widodo (Dept. of Chemical Engineering, Diponegoro University, 2002)
The sourcing lifetimes, microstructural staility, and diffution performance of a new solid planar phosphorus source for silicon doping were investigated in the temperature range 900-1000 0C. The source wafers were highly porous ceramic wafers containing 25 weight percentage (w/o) SiP2O7 as the “active” component in an inert refractory binder matrix. The microstructural stability and thermografimetric analysis (TGA) result indicated the structural integrity and sourcing ability of this materials at temperatures of at least 1050 0C. Theoretical lifetimesof 260 and 3400 hr at 1000 and 900 0C, respectively, have been predicted from the TGA results. Experimental data relating sheet resistance, junction depth, and diffution coefficient for silicon wafers doped using these source wafers are presented. Special material handling procedure are also described. Keywords : diffution process, solid phosphorus source, SiP2O5, semiconductor devices